The Effect of Sea Water Sea Sand Mixed Self Compacting Concrete Infrastructure development in coastal areas and isolated islands - Adnan Adnan; Jasman Jasman; Salasiah Salasiah; Miswar Tumpu (Proceeding of the International Conferences on Engineering Sciences, 2024)
The United Nations and the World Meteorological Organisation predict that around 5 billion people will lack clean water and even drinking water (Source: Conference on Our World in Concrete and Structure in Singapore). Based on the aforementioned phenomenon, given the abundant potential of seawater resources, there is an idea to use seawater as a concrete admixture, especially in building locations that often interact with seawater. Research is carried out in an effort to find alternatives to improve the mechanical properties of concrete such as compressive strength values, split tensile strength, namely by using additives as self-compacting concrete technology and making seawater and sea sand as a substitute for fresh water and river sand